Effectiveness Of Warm Ginger Milk Consumption In Reduce Emesis Gravidarum In 1st Trimester Pregnant Women In Pmb Karawang City Year 2023 - Rismayanti, Tetin; Ratnaningsih, Romih (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: In early pregnancy, many mothers experience complaints of nausea, vomiting, especially in the morning, which is known as morning sickness or in medical language known as emesis gravidarum. Symptoms of emesis gravidarum in pregnant women can be treated both with conventional and non-conventional treatments or often referred to as complementary therapy, namely with herbal plants that are easily available such as lemongrass, lemon, peppermint leaves and the most popular is ginger. Research Objectives: To determine the effectiveness of consuming warm ginger milk juice in reducing emesis gravidarum in first trimester pregnant women at PMB Karawang City in 2023 Research Methods: The type of research used in this study is quasi-experimental and post test only design one group. The population in this study were 54 mothers. The sample in this study were 35 mothers who were in PMB Karawang City. Bivariate analysis using the Wilcoxon test. Results: The average frequency of emesis gravidarum in 1st trimester pregnant women before being given warm ginger juice was 9.97, a standard deviation of 1.636, a minimum of 7 and a maximum of 13. The average frequency of emesis gravidarum in 1st trimester pregnant women after being given consumption warm ginger milk juice is 5.54, a standard deviation of 1.039, a minimum of 4 and a maximum of 7. Conclusion: It can be concluded that consumption of warm ginger milk juice is effective in reducing emesis gravidarum in first trimester pregnant women at PMB Karawang City in 2023.